THE EFFECTS OF FEEDING DIETS CONTAINING SEA-GRASS ON THE FINAL BODY WEIGHT, CARCASS PERCENTAGE, AND ABDOMINAL FAT OF BROILERS - S. Pantjawidjaja (Jurnal Ilmu dan Teknologi Peternakan, 2011)
This study was carried out to investigate the effects of feeding diet without sea-grass (control) and diets containing sea-grass (4.5% Euchema cottonii or 4.5% Gracillaria verucosa) on final body weight, carcass percentage and the abdominal fat of  broilers. Fifty-four 1-day-old SUR-707 unisex broiler chicken, were randomly placed into 18 cages and fed isocalorie-isoprotein diets containing 4.5% of two different sea-grass sources (Eucheuma cottonii  or Gracilaria verrucosa) and control. Parameters observed were production performance of broiler. Body weight was measured by the live weight of the birds at 42 days, end of study period. After slaughtering, birds were processed for carcass weight. Abdominal fat as part of waste was measured by weight and carcass percentage was expressed as the ratio of carcass weight and final body weight times 100%. The results showed that treatments had no significant effects (P>0.05) on all parameters.  Although the differences were not statistically different, the results showed numerical differences for all parameters. In conclusion, sea-grass treatments have a tendency to produce higher carcass percentage and lower abdominal fat than diet without sea-grass (control).